Effects of the Environmental Strategy and Management Control System Package on Managerial Performance - Beuren, Ilse M.; Vaz, Patricia V. C. (Journal of Environmental Accounting and Management, 2026)
This study examines the effects of the environmental strategy and the Management Control System (MCS) Package on management performance in Brazilian companies. A questionnaire prepared by Roetzel et al (2014) was applied to the companies listed as the 150 best companies to work in Brazil, and the sample consists of 73 respondents. Structural equation modeling was used to analyze the hypotheses. The environmental strategy positively influences the MCS Package. The MCS Package positively influences managerial performance. It was also found that cybernetic and cultural controls are the package’s most comprehensive elements of MCS, a result that is consistent with Roetzel et al (2014), however, in the Brazilian scenario, were the administrative controls and not the remuneration and rewards that demonstrated less important role. The analysis of the interaction of these elements can instigate managers as to the importance of studying environmental issues in the Brazilian scenario, in order to broaden the discussion on an integrated environmental policy. Analysis of the effects of the environmental strategy and the MCS Package on management performance contribute to the consolidation of theoretical principles and can be essential for proposing sustainable development policies. Although these interactions were tested in the study by Roetzel et al (2014), the perception of managers may differ in contexts with different environmental management strategies.